Trading Activities and Lived Experiences of Chinese Immigrant Traders in Ghana - Narh, C. (University of Ghana, 2022)
In the last two decades, international migration has seen an unprecedented increase, especially between South-South economies. As a result, Chinese citizens are increasingly migrating to Ghana to engage in trading activities with the expectation of consolidating their gains in international trade volumes. However, in recent times, there have been rising tensions between Ghanaian traders and Chinese immigrant traders which require a critical understanding of the trading experiences of Chinese immigrant traders, as well as the Ghanaian trading community to align trade interests for mutual benefits. This study therefore examines the trading activities and lived experiences of Chinese immigrant traders based on the attitudes that Ghanaian traders have towards Chinese immigrant traders. Using random, purposive, and snowballing sampling techniques to select 529 participants from Accra and Kumasi, the study used a mixed-method approach to examine the influence of trading activities on lived experiences of Chinese immigrant traders. Based on the logistic regression analysis, the study results show that the most important factors influencing the lived experiences of Chinese immigrant traders are retail trading activity, economic incentives, length of stay in Ghana, level of education and location. Considering trading activity, the study finds that Chinese retailers are 32% less likely to have a “very good” relationship with Ghanaian traders. This finding is indicative of the prevalence of tensions between Ghanaian and Chinese traders. Aside from retailing, factors such as quality of goods, price competitions, and fronting are associated with the rising tensions between Ghanaian and Chinese traders. Thus, the study concludes that trading activity (i.e., retail or wholesale) play a significant role in shaping lived experiences of Chinese immigrant traders.
PhD. Migration Studies
Keywords: international migration; Chinese citizens; Ghana